Young immigrants’ access to education and vocational training. An assessment of the Constitutional Court Judgement 236/2007 and the vocational and professional training reform - Moya, David (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
As a mean to ensure social cohesion and immigrants’ integration, Spanish Society and its Public Administration should grant immigrant children full access to education and vocational and professional training, at least on an equal footing with Spanish nationals. Furthermore, there are strong reasons to consider the creation and deployment of a pull of services aimed at granting children quick access to education and vocational training in certain situations, independently of their legal status. At present, apart from a Constitutional Court decision allowing minors in administrative irregularity to accede to these services, Spanish legislation is not clear about their rights. Without a solid legal basis, Regional and Local Administrations are reluctant to adapt their educative systems to integrate immigrant young people and to promote the acquisition of the necessary professional skills to accede to the labour market and, eventually, regularize their administrative status